2006
DOI: 10.1063/1.2179412
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel instrument for microwave dielectric thermal analysis

Abstract: The advantages of microwave heating in industrial processing are becoming more widely appreciated and the technique is of increasing commercial significance. However, knowledge of a material's dielectric properties as a function of temperature is of considerable importance as they determine the efficiency with which the material converts microwave energy into heat. This article describes the development of a novel instrument for a new form of thermal analysis, microwave dielectric thermal analysis ͑MDTA͒ in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…As per Eq. 2 , the power dissipated ( P d ) from microwave absorption is in terms of watts/m 3 and is proportional to a constant K , the dielectric constant ɛ , the loss factor tan( δ ), the microwave frequency f , and the electric field E ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…As per Eq. 2 , the power dissipated ( P d ) from microwave absorption is in terms of watts/m 3 and is proportional to a constant K , the dielectric constant ɛ , the loss factor tan( δ ), the microwave frequency f , and the electric field E ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…With the use of tablets of paracetamol and hyproxypropyl methylcellulose, it is demonstrated that the technique is capable of differentiating between the components in scanning mode, whereas three-dimensional imaging can be accomplished by allowing the probe to melt through the paracetamol down to the underlying polymer. Nair et al (34) have developed a novel instrument for a new type of thermal analysis, microwave dielectric thermal analysis, in which dielectric properties of a sample are determined while it is heated by microwaves. A plot of the dielectric properties against temperature allows one to observe the effect of the temperature as well as of chemical and/or physical changes on material's dielectric properties (both the real and imaginary parts of the complex permittivity).…”
Section: Methods Development and Calibrationsmentioning
confidence: 99%